2008
DOI: 10.1111/j.1365-2354.2007.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and dyadic adjustment in oral cancer patients and their female partners

Abstract: The diagnosis of cancer affects not only the lives of patients, but also the lives of their family members. The purpose of this study was to examine the impact of oral cancer on quality of life (QoL), psychological distress and marital satisfaction in a sample of patients and their wives. Thirty-one men treated for oral cancer (mean time since diagnosis 3.7 years) and their female partners (n = 31) were assessed by questionnaires with regard to QoL (WHOQOL-BREF), anxiety and depression (Hospital Anxiety and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 34 publications
6
50
0
4
Order By: Relevance
“…In contrast, advanced-stage carci noma patients show a subjective QoL that seems significantly lower as compared to ALS patients (Fegg et al, 2005) and which continues to decline as the disease leads to progressive physical impairment (Frick et al, 2007;Jenewein et al, 2008). Patients with severe paralysis leading in its most extreme form to a LIS seem to experience a subjective QoL that is better than that of patients with terminal cancer, and comparable to that of patients with nonterminal chronic disease (McGee et al, 1991;Moons et al, 2004).…”
Section: Quality Of Lifementioning
confidence: 82%
“…In contrast, advanced-stage carci noma patients show a subjective QoL that seems significantly lower as compared to ALS patients (Fegg et al, 2005) and which continues to decline as the disease leads to progressive physical impairment (Frick et al, 2007;Jenewein et al, 2008). Patients with severe paralysis leading in its most extreme form to a LIS seem to experience a subjective QoL that is better than that of patients with terminal cancer, and comparable to that of patients with nonterminal chronic disease (McGee et al, 1991;Moons et al, 2004).…”
Section: Quality Of Lifementioning
confidence: 82%
“…Developed by the researchers upon the literature review [10,12,21,23] the questionnaire consisted of 20 questions examining the patients' socio-demographic characteristics (age, gender, educational level, income, marriage duration and type) and disease-related information (duration to diagnosis, duration of HD, additional chronic diseases, etc. ).…”
Section: Patient Information Formmentioning
confidence: 99%
“…Numerous studies have revealed that chronic diseases lead to serious impairments in the marital relationships [10][11][12]. Chronic diseases can directly affect the marital adjustment of the couples as a result of the related symptoms and complications [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Mit seiner Konzeptualisierung der "Alexithymie" schuf Sifneos die Voraussetzungen zur Operationalisierung eines multidimensionalen Persönlichkeitskonstrukts, das durch die Schwierigkeit, Gefühle wahrzunehmen und zu kommunizieren, und eine reduzierte Fähigkeit zu fantasieren, die sich auch in einer Tendenz zu external orientiertem Denken ausdrückt, charakterisiert ist [26]. Die Entwicklung entsprechender valider Messinstrumente ermög-lichte, Zusammenhänge zwischen alexithymen Persönlichkeitsmerkmalen und verschiedenen Erkrankungen empirisch zu untersuchen [7,14,28]. Dadurch konnte ein Zusammenhang zwischen Alexithymie und Somatisierung empirisch in der Allgemeinbevölkerung [18] sowie bei Patienten mit somatoformen und funktionellen Störungen [31] untersucht und im Verlauf der Zeit mehrfach bestätigt werden.…”
Section: Lebensqualität Und Alexithyme Merkmale Bei Patienten Mit Somunclassified
“…(SD=20,89). Auch im Vergleich zu Patienten mit Mundhöhlenkrebs, die z. T. mit erheblichen krankheitsbedingten Behinderungen und der Ungewissheit einer lebensbedrohlichen Erkrankung leben müs-sen, wiesen die Schmerzpatienten eine deutlich reduzierte QoL auf [14]. Obwohl ein direkter Vergleich aufgrund der unterschiedlichen Gruppencharakterisierung schwierig erscheint, ist die Beeinträchti-gung der allgemeinen gesundheitsbezogenen QoL der untersuchten Schmerzpatienten beachtenswert.…”
Section: Diskussionunclassified